Fashion Business Leadership - DM293 - 202301 - Mendizabal Olaechea, Rossana (2023)
This subject is an elective specialty course in the Fashion Design and Management career. It a theoretical- practical course aimed for students coursing the ninth semester that articulates the main competence of Critical Thinking and Communication and the specific competence of Strategic Management. To be successful in the fashion world, and be ahead of the changing and diverse scenarios, it is required to have the knowledge and tools that allows one to act and develop with security, decision, confidence, initiative, commitment and values, and to have an entrepreneurial and innovative attitude in life. For this reason, this course is designed so that you can develop your potential as a leader in the professional environment in which you operate, so that you acquire this knowledge, skills, and abilities in order to encourage, inspire and motivate your collaborators to innovate and create changes that help grow and shape the future success of your company. This course is designed for you to develop your skills with a strategic leadership vision, to build high performance environments through time management, decision making, problem solving and future planning of the organization, without losing the focus on objectives, a sense of belonging, and influencing and involving your team in decision-making, problem-solving capacity, among others.